Mandibular-Lingual Repositioning Device - MLRD: preliminary results of 8 patients with Obstructive Sleep Apnea Syndrome - OSAS - Barbosa, Ricardo Castro; Aloe, Flávio; Tavares, Stella; Silva, Ademir Baptista (São Paulo Medical Journal, 1995)
Dental devices have been employed in the treatment of snoring and obstructive sleep apnea syndrome (OSAS) of mild to moderate degrees. The authors disclose the preliminary results in 8 patients with clinically diagnosed obstructive sleep apnea polisomnographically confirmed and treated with a dental device (Mandibular-Lingual Repositioning Device - MLRD) developed by one of the authors (RCB). Cephalometrics was performed before usage of MLRD, Epworth Sleepiness Scale (ESS) tests were conducted before and after the MLRD and a questionnaire that subjectively qualified the Overall Subjective Improvement of the patient (OSI) was filled out. The tests were repeated 4 weeks after the application of the MLRD. The average subjective overall improvement was 73.75% and the Epworth Sleepiness Scale was 13.88 (pre - MLRD) and 6.63 (post - MLRD) representing a significant statistical variation (p=0.05). The authors discuss probable factors involved in the improvement of the subjective measurements of excessive sleepiness.